Question

\[ \text{¿Cuál es } 2011^2 - 2010^2 \text{?} \]

Ask by Bernard Smith. in Colombia
Feb 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La respuesta es 4021.

Solution

Podemos resolverlo usando la identidad de diferencia de cuadrados:   a² - b² = (a + b)(a - b). En este caso, a = 2011 y b = 2010. Entonces:   2011² - 2010² = (2011 + 2010)(2011 - 2010) = (4021)(1) = 4021. La respuesta es 4021.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

¡Vamos a desglosar esto como si estuvieras sacando el postre de una caja de chocolates! La expresión que tienes es una diferencia de cuadrados, que se puede expresar como \(a^2 - b^2 = (a - b)(a + b)\). Así que sustituyendo, donde \(a = 2011\) y \(b = 2010\), obtenemos: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \times 4021 = 4021 \] Así que \(2011^2 - 2010^2 = 4021\). ¡Sorpresa! Además, es fascinante notar que esta fórmula se puede aplicar a cualquier par de números consecutivos. Por ejemplo, si quieres calcular \(n^2 - (n-1)^2\), siempre obtendrás \(2n - 1\). Así que, para \(n = 2011\), ¡aquí va la confirmación! El resultado sigue siendo 4021. ¡Queda claro que las matemáticas siempre tienen un truco bajo la manga!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy